2008
DOI: 10.1016/j.chom.2008.07.008
|View full text |Cite
|
Sign up to set email alerts
|

Acyclovir Is Activated into a HIV-1 Reverse Transcriptase Inhibitor in Herpesvirus-Infected Human Tissues

Abstract: SUMMARY For most viruses, including HIV, there is a need for antimicrobials that target unique viral molecular properties. Acyclovir (ACV) is such a drug for human herpesviruses (HHVs): it is activated into a HHV-DNA polymerase inhibitor exclusively by HHV-kinases and thus does not suppress other viruses. Here, we report on the direct inhibition of HIV-1 reverse transcriptase (RT) by phosphorylated ACV, which terminates DNA chain elongation and can trap RT at the site of termination. Consequently, ACV suppress… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
125
2
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 110 publications
(134 citation statements)
references
References 41 publications
6
125
2
1
Order By: Relevance
“…One key finding from these studies was that the anti-HIV-1 activity of acyclovir is HSV-2 independent. Lisco et al quantified levels of HHV in tonsil samples used in HIV-1 infection assays and found HHV-6 present in all samples where acyclovir inhibited HIV-1 replication (17). This finding suggests that coinfection with an HHV is necessary for the anti-HIV-1 activity of acyclovir.…”
mentioning
confidence: 90%
See 2 more Smart Citations
“…One key finding from these studies was that the anti-HIV-1 activity of acyclovir is HSV-2 independent. Lisco et al quantified levels of HHV in tonsil samples used in HIV-1 infection assays and found HHV-6 present in all samples where acyclovir inhibited HIV-1 replication (17). This finding suggests that coinfection with an HHV is necessary for the anti-HIV-1 activity of acyclovir.…”
mentioning
confidence: 90%
“…Quantitative real-time PCR was performed to determine if known HHVs were present in CD4 ϩ T lymphocytes used in the singleround infectivity assays. To do this, we isolated cellular DNA from ϳ5 ϫ 10 6 CD4 ϩ T cells from each donor and used herpesvirus-specific primer and probe sets as reported by Lisco et al (17) in individual PCR mixtures containing DNA from ϳ150,000 to 250,000 CD4 ϩ T cells. As shown in Table 1, all adult blood donors had detectable levels of the T-cell-tropic HHV-6 and -7, with HHV-7 being present in Ͻ0.3% of cells.…”
Section: Fig 1 Acyclovir Is An Anti-hiv-1 Drug (A) Enzymes That Phmentioning
confidence: 99%
See 1 more Smart Citation
“…The most prevalent sexually transmitted diseases are AIDS and herpes simplex virus (HSV) infection, which are caused by two opportunistic pathogens and lead to progressive failure of the immune system (1). Globally, over 33 million individuals are infected with HIV, and AIDS continues to date to be the most destructive known pandemic.…”
Section: Introductionmentioning
confidence: 99%
“…The placebo gel used in the trial was the "universal" HEC placebo gel, which has been shown to have minimal anti-HIV activity (6). We hypothesize that our patented bioadhesive formulation (7), composed of two FDA-approved polymers, Pluronic® F-127 (polyoxyethylene polyoxypropylene co-polymer, polaxomer) and Noveon® AA-1 (polyacryclic acid), will [1] be a more efficacious platform for delivery of the antiviral drugs tenofovir and acyclovir, [2] offer protection against viral infection, and [3] have a long residence time because it will form micelle-like particles that adhere to the vaginal wall. The epithelium of the vagina contains glycogen, which is broken down by enzymes and bacteria into lactic acid to maintain low vaginal pH between 4 and 5, which is inhospitable to pathogens (8).…”
Section: Introductionmentioning
confidence: 99%